R-SUBGRUP NORMAL FUZZY NEAR-RING - Saman Abdurrahman (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2011)
In this paper will be discussed R-subgroup normal fuzzy near-ring, with approach and    + 1  , for each .